Uma sequência didática para o ensino de ondas: o uso de um jogo didático para mediação de conceitos - Félix, José Charles dos Santos (2025)
This work aims to investigate the application of didactic sequences and educational games in teaching the topic of waves, based on Vygotsky's learning theory, within the context of the National Network for the Graduate Program in Physics Teaching. The study involved the creation of a didactic sequence and an evaluative educational game for high school students. The research was divided into two stages: the first consisted of a theoretical review, including bibliographic studies on wave teaching, Vygotsky's theory, and the use of educational games; the second involved practical application at the Francisco de Assis Bittencourt Full-Time State High School in João Câmara – RN. The didactic sequence was designed and implemented in a 2nd-year high school class, consisting of up to 40 students, and was delivered over four 50-minute lessons. The physical game, called Cool Waves, is a quiz focused on teaching Physics, specifically the topic of waves, aiming to be a mediating tool that supports the development of physical concepts.